Development of polar order in liquid crystalline phases of a banana compound with a unique sequence of three orthogonal phases - VIJ, JAGDISH KUMAR; PANARIN, YURI PETROVICH (Royal Society of Chemistry, 2010)
Alkyl substituted 4-cyanoresorcinol 1,3-bisbenzoates with terephthalate based rod-like wings show a series of three orthogonal smectic phases SmA?SmAPR?SmAPA.
PUBLISHED
Keywords: 4-cyanoresorcinol 1,3-bisbenzoates; Chemistry